Nutrients in Water Masses in the Atlantic Sector of the Arctic Ocean: Temporal Trends, Mixing and Links With Primary Production. Issue 8 (30th July 2021) - Duarte, Pedro; Meyer, Amelie; Moreau, Sebastien
Abstract: There is strong evidence of an increase in primary production (PP) in the Arctic Ocean (AO) over the last two decades. Further increases will depend on the interplay between decreasing light limitation for primary producers, as the sea ice extent and thickness decrease, and the availability of nutrients, which is controlled by, but not limited to, inputs from the Atlantic and the Pacific Oceans. While these inputs are the major nutrient sources to the AO, ocean vertical mixing is required to bring the nutrients into the photic zone. We analyze data collected in the Western Eurasian Basin (WEB) between 1980 and 2016 and characterize the nutrient climatology of the various water masses. We conclude that there were no significant trends in the concentrations of the two macronutrients that typically limit PP in the AO (nitrate and silicic acid, in the case of diatoms), except a decreasing trend for silicic acid in Polar Surface Water (PSW), which is consistent with the reported increase in PP in the AO. We suggest that the Whalers Bay polynya, located in the northwestern corner of Svalbard, may act as a mixing hotspot, creating patches of nutrient replenished PSW. These patches may then be advected to higher latitudes under the ice pack, later boosting PP upon release from light limitation or else, keeping a nutrient reservoir that may be used in a subsequent growth season. It is likely that this remaining nutrient reservoir will decrease as sea ice cover retreats and light limitation alleviates. Plain Language Summary: There is strong evidence of an increase in primary production (PP) in the Arctic Ocean (AO) over the last two decades. This has strong implications for global biogeochemical cycles and on how the AO mitigates the increase in greenhouse gases. However, predicting how much PP will further increase depends on the interplay between decreasing light limitation for primary producers, as the sea ice extent and thickness decrease, and the availability of nutrients, such as nitrate, phosphate, and silicic acid (abbreviated as silica). We analyzed data collected over more than three decades in the Western Eurasian Basin (WEB) of the AO (1980–2016). We conclude that the nutrient concentrations of the various water masses found in this area have not changed significantly, except for the surface water masses, where there is a decreasing trend in silica concentration. This trend is consistent with the reported increase in PP. Our study provides a baseline for the nutrient composition of the water masses found in the WEB to follow their changes in the near future. Key Points: There are no long‐term trends in nutrient concentrations except for decreasing silicic acid in Polar Surface Water Silicic acid is the main limiting nutrient for diatom production yields The nutrient contents of the water masses found in the Western Eurasian Basin is quite predictable